2019
DOI: 10.1002/mds.27936
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physiotherapy on Freezing of Gait in Parkinson's Disease: A Systematic Review and Meta‐Analyses

Abstract: A BS TRACT: Freezing of gait is considered one of the most disabling gait disorders in patients with PD. An effective treatment for freezing of gait is missing, thus current management requires a multidisciplinary approach. Among treatment options, physiotherapy is acknowledged to be crucial; however, a systematic review that demonstrates its efficacy is missing. This review aims at examining the short-and long-term effects of physiotherapy in improving freezing of gait in PD patients. Five electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 60 publications
(487 reference statements)
2
58
2
5
Order By: Relevance
“…Apart from cues, treadmill training [164][165][166][167][168], obstacle aquatic training [169], supervised slackline training [170], walk-bicycle [171], and action observation [172,173] have also shown positive effects on FOG. Recently, Cosentino C et al [174] performed a systematic review and metaanalysis to evaluate the effectiveness of physiotherapy intervention on FOG symptoms. A total of 19 studies, including 913 patients, were enrolled and FOGQ was used as the primary outcome measure.…”
Section: Physiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cues, treadmill training [164][165][166][167][168], obstacle aquatic training [169], supervised slackline training [170], walk-bicycle [171], and action observation [172,173] have also shown positive effects on FOG. Recently, Cosentino C et al [174] performed a systematic review and metaanalysis to evaluate the effectiveness of physiotherapy intervention on FOG symptoms. A total of 19 studies, including 913 patients, were enrolled and FOGQ was used as the primary outcome measure.…”
Section: Physiotherapymentioning
confidence: 99%
“…However, the efficacy of various cueing devices need to be further tested outside the home or laboratory and in a larger PD patients with FOG. Apart from cues, a systematic review and meta-analysis found that action observation, treadmill combined with cueing, and prolonged homebased exercise trainings were able to impact on FOG more than other approaches [174].…”
Section: Summary Of Non-pharmacological Treatments For Fogmentioning
confidence: 99%
“…Consequently, studies aimed at investigating the effects of AOT on motor and functional abilities have been published over the past years, suggesting that AOT improves autonomy, walking ability, or typical motor signs such as freezing of gait and bradykinesia in patients with PD ( 17 20 ); however, a systematic review on this topic is missing. In particular, a single meta-analysis investigating the effectiveness of physiotherapy in these patients have reported positive results of AOT on freezing of gait ( 21 ), but the efficacy of this innovative tool on other functional outcome measures adopted in rehabilitation of patients with PD has never been systematically quantified. Moreover, AOT can be delivered alone or in association with usual physiotherapy through video-clips representing motor contents ( 20 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tatsächlich gibt es dabei einen sehr guten Nachweis, dass gezielte Physiotherapie gerade das FOG positiv beeinflussen kann. Zwei Meta-Analysen fassen die positiven Effekte der derzeit existierenden kontrollierten Studien zusammen [69,70]. Dabei wurden verschiedene physiotherapeutische Strategien einbezogen: visuelles und auditorisches Cueing-Training, Balance-Training, Heim-basiertes Bewegungstraining, Bewegungsbeobachtung/-nachahmung ("Action observation"), Aqua-Training und Laufband-Training bis hin zum überwachten Slackline-Training [69].…”
Section: Physiotherapie Für Freezing-of-gaitunclassified
“…Zwei Meta-Analysen fassen die positiven Effekte der derzeit existierenden kontrollierten Studien zusammen [69,70]. Dabei wurden verschiedene physiotherapeutische Strategien einbezogen: visuelles und auditorisches Cueing-Training, Balance-Training, Heim-basiertes Bewegungstraining, Bewegungsbeobachtung/-nachahmung ("Action observation"), Aqua-Training und Laufband-Training bis hin zum überwachten Slackline-Training [69]. Speziell die auf das individuelle FOG der Patienten zugeschnittenen Therapieformen erzielten in den Meta-Analysen sehr gute Effekte im Vergleich zur Standard-Physiotherapie.…”
Section: Physiotherapie Für Freezing-of-gaitunclassified